The various influence of changes of the suspensions concentration on the process of their sedimentation - Kowalski, W.; Banaś, M. (Видавництво Національного університету “Львівська політехніка”, 2005)
A research of the grain constitution of the polidyspersant suspension as a function of its concentration is presented. Both the theoretical deliberation and the laboratory research have confirmed, that – at a certain range of concentration – an increase of the particles’ settling velocity occurs, which is raising the sedimentation efficiency. That increase may even decrease the particles’ concentration in the cleared suspension in spite of the increase of the concentration of the solid phase particles in the suspension being cleared.